2019
DOI: 10.1080/01900692.2019.1570523
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and Integrating Policies on Performance-Based Pay: Coordinating the “One-Employer Approach” in a Swedish Municipality

Abstract: In Sweden, performance-based pay has gone furthest in the public sector. This development has placed demands on employers to have a transparent and salient salary review process with which to evaluate employees uniformly and fairand to act in a unitary manner, as one employer. Pay policies aim to coordinate salary reviews in organizations. However, the transfer of policy to practice is not easy and research has shown a gap between intended and implemented policies. Drawing on a case study in a municipality, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…However, processes of individualization are nonetheless present. Decades of decentralization of collective bargaining have institutionalized individualized wage setting, which has particularly affected the public sector (Kjellberg, 2019;Ulfsdotter Eriksson et al, 2021). Most collective agreements statue the right to yearly salary negotiation.…”
Section: The Swedish Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…However, processes of individualization are nonetheless present. Decades of decentralization of collective bargaining have institutionalized individualized wage setting, which has particularly affected the public sector (Kjellberg, 2019;Ulfsdotter Eriksson et al, 2021). Most collective agreements statue the right to yearly salary negotiation.…”
Section: The Swedish Contextmentioning
confidence: 99%
“…Most collective agreements statue the right to yearly salary negotiation. However, the scope for the negotiation is limited by a normative use of wage raises in the industry (the "mark") as the benchmark, and limited local pots for wages, creating a zero-sum game where giving a reward to one employee reduces the availability of raises for the others (Ulfsdotter Eriksson et al, 2021). Hence, as individualized wage setting co-exist with collective regulations, the prevalence and impact of individual arrangements might be less distinct than in other contexts.…”
Section: The Swedish Contextmentioning
confidence: 99%
“…When the fieldwork was conducted, they had specified the general criteria only for childcare in which they had slightly different wordings in the criteria for pre-school teachers and child-minders. A survey study conducted showed that about 40% of the employees had specified ones and equally many used the general appraisal criteria (Ulfsdotter Eriksson et al 2019).…”
Section: Materials -Performance Appraisal Criteriamentioning
confidence: 99%
“…The state agency and the municipality use 'professionalism' as the main criterion for quality and, for the latter, 'high quality' is the main part of the definition of the 'professionalism criterion'. Professionalism is a common performance criterion (Ulfsdotter Eriksson et al 2019) and a prevalent value in organizations more generally. Also, and as discussed by Fournier (1999) and Evetts (2011), professionalism is increasingly used as a discursive device to manage, control, and discipline employees.…”
Section: The Industrial World Of Worthmentioning
confidence: 99%